THE APPLICATION OF EXPERIMENT LEARNING ON THE LEARNING MATERIAL THE INFLUENCE OF LEARNING MODEL CTL (CONTEXTUAL TEACHING AND LEARNING) WITH ASK-AND-ANSWER METHOD FOR BASIC COMPETENCE TO EXPLAIN FUNCTION AND CONSTRUCTION OF BATTERY ON STUDENT STUDY RESULT - Sukamdani; Debora (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2015)
The purpose of this study is to determine whether there is a difference in student learning outcomes by using CTL learning model and conventional methods. Benefit taken from this research is that it can provide inputs on the theory of learning and the use of variations in learning about the learning function and construction of battery with CTL learning model. This research is an experimental research design with post test only control design. After doing research on the results of post test of experimental group and the control group, normality test and homogeneity test were done as test requirements as a condition analysis prior to test of the hypothesis. Posttest results obtained from the data shows that the experiment group and the control group have normal distribution and homogeneous. Based on the results of hypothesis testing using t-test, it was obtained tcalculated = 15.43, while ttable = 2.032 at significance level of 5% = 0.05 and df = (18 + 18-2) = 34. It can be seen that tcalculated > ttable, then Ho is rejected and Hais accepted. Thus it can be concluded that there is significant influence on student learning outcomes between using CTL with those that use conventional learning model on the competency in explaining about the functions and construction of battery in class X TKR SMK B1 Palangka Raya.